Language Subject Access to Indigenous Materials: The Philippine Cordillera Case - Villanueva, Cristina B. (Cataloging & classification quarterly, 2022)
Limitations of the Library of Congress Subject Headings (LCSH) in assigning subject access terms for Philippine Cordillera materials are presented. A number of Indigenous terms that have no American or English language equivalent are described, as well as issues with spelling variations, nomenclature, and local terms in the different languages and dialects. With the cataloging and indexing policy of University of the Philippines System Libraries adopting the use of LCSH and assigning broader concepts to local terms when no translation and specific representations exist, low findability of materials is expected. Steps to address the problems and solutions to improve searching are discussed and recommended.